In-soil strength and behaviour of geosynthetic reinforcements - Yardımcı, Tolga. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In this study, in-soil tensile strength and behaviour of various geosynthetic re inforcements is investigated with the help of custom designed and developed in-soil tensile test apparatus in the laboratory. The proposed apparatus, which can simulate the site conditions, is considered an alternative to wide width tensile test apparatus. Displacement controlled in-air and in- soil tensile tests were conducted to investigate the influence of soil type, normal stress and presence of the passive reinforcement (re inforcement located above and below the test reinforcement) on the tensile strength and behaviour of various geosynthetics. Three geosynthetics (nonwoven geotextile, wo ven geotextile and geogrid) and two soil types (Well Graded Sand and Well Graded Gravel with Sand) are used in the study. Normal stress used in the study ranges from 25 to 75 kPa. A constant strain rate of 2% strain/min was applied in all tests. All geosynthetics tested in soil under normal stress were found to have an improvement in tensile load-strain behaviour. The increase in the stiffness was formulated to quantify the improvement in the behaviour and to reduce carrying out further tests. Gravel was found more effective on influencing the behaviour when compared to the sand. In sand, using passive reinforcements obviously decreases the tensile load-strain behaviour of the geosynthetics while it has various effects in gravel.
Keywords: Geosynthetics.